Analyzing Research Trends and Future Directions in Entrepreneurship Education with a Bibliometric approach - Judijanto, Loso; Baruno, Yosep Heristyo Endro; Halim, Chandra (The Eastasouth Journal of Learning and Educations, 2024)
This study provides a comprehensive bibliometric analysis of the literature on entrepreneurship education, examining research trends, thematic clusters, research opportunities, and author collaboration from 2014 to 2018. Utilizing VOSviewer, the study identifies key themes and shifts in academic focus over the years, with an emphasis on topics such as entrepreneurial mindset, innovation, social entrepreneurship education, gender dynamics, and self-efficacy. The analysis highlights the central role of entrepreneurship education within the broader educational discourse and its integration into higher education frameworks. Notable research clusters led by influential scholars such as Alain Fayolle and Harry Matlay are mapped, revealing strong internal collaborations and suggesting potential for increased cross-disciplinary research. The findings underscore the need for interdisciplinary approaches, the integration of technology in educational practices, and the development of inclusive programs tailored to diverse demographics. This study provides valuable insights for educators, policymakers, and researchers aiming to enhance the effectiveness and reach of entrepreneurship education.